2018
DOI: 10.1007/s10802-018-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Psychopathic Traits in a Community Sample of Youth

Abstract: The current study aims to address socioeconomic status (SES) as a moderating variable between psychopathic traits and conduct problems in a sample of 2432 Dutch adolescents (Mage = 14.50 years, SD = 1.67, 56% male). Both family and neighborhood SES were measured, with income as a proxy for the level of SES. There were small but significant positive correlations between the behavioral and interpersonal dimensions of psychopathy and family SES, a small but significant negative correlation between the affective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…In addition, the age range in our study was 1.55 to 12.92 years, whereas some other studies have focused only on adolescents. 37 Finally, a unique aspect of this study is its focus on the patterns of changes in emotional and behavioral problems, whereas past studies have investigated only the levels of such problems. Studies on factors affecting changes in emotional and behavioral problems are scarce, particularly those focusing on children with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the age range in our study was 1.55 to 12.92 years, whereas some other studies have focused only on adolescents. 37 Finally, a unique aspect of this study is its focus on the patterns of changes in emotional and behavioral problems, whereas past studies have investigated only the levels of such problems. Studies on factors affecting changes in emotional and behavioral problems are scarce, particularly those focusing on children with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Walsh and Kosson (2007) found that lower family SES was predictive of violent reoffending recidivism among European American psychopathic individuals (medium effect size), but not for African Americans. In a sample of adolescents, neither family SES nor individual SES moderated the relationship between psychopathy and conduct problems (Zwaanswijk et al, 2018). However, because conduct problems are part of the criteria for psychopathy, it is possible that the overlap between the predictor and outcome variables influenced these results.…”
Section: Introductionmentioning
confidence: 99%
“…focus on other aspects related to human diversity that have not been addressed in the present study; for instance, socioeconomic status is a variable that affects many aspects of the quality of parent-child attachment relationship -including attachment (e.g., Eckstein-Madry et al, 2021;Puckering, 2004), while its role in CU traits or psychopathic is still debated (e.g., Markowitz et al, 2015;Zwaanswijk et al, 2018). Once again, future research could consider to which extent students' socioeconomic status moderates and/ or mediates the associations between attachment styles and CU traits.…”
Section: Resultsmentioning
confidence: 99%